FIRM CHARACTERISTICS AND PROFITABILITY OF LISTED INDUSTRIAL GOODS COMPANIES IN NIGERIA: THE MODERATING EFFECT OF FIRM SIZE - Idogho, Abraham Momoh; Ebogbue, Celestine Chukwutem; Onmonya, Lucky; Bosun-Fakunle, Yemisi Funmilayo (International Journal of Accounting & Finance Review, 2024)
Corporate success is measured by profitability, an important metric, influenced by various factors, including the firm’s size, with multiple effects. The firm’s size, however, as a moderating factor, adds complexity, potentially altering the relationship between firm characteristics and profitability, especially within Nigeria’s industrial goods sector. This study examined the impact of firm characteristics and profitability of listed industrial goods companies in Nigeria. As a moderating factor, firm characteristics were represented by liquidity, leverage, and firm age, while the return on assets measured profitability. The study data was collected from ten listed industrial goods firms that had consistently published their audited annual financial reports from 2013 to 2022. The panel-corrected standard error for the random effect model was used to analyze the data. The results show that liquidity has a negative and significant effect on profitability. Conversely, leverage and firm age have a positive and insignificant impact on profitability. In evaluating the moderating effect of firm size, the panel regression results conclude that firm age can reduce profitability. However, the analysis also revealed that liquidity has a positive and insignificant effect on profitability when moderated by firm size while leverage has a negative and insignificant result on profitability. On the other hand, firm size significantly moderates the relationship between firm characteristics and profitability. The findings of this study recommend that younger listed industrial goods firms should not be discouraged by the negative effect of their age on profitability rather they may be profitable as they grow old. JEL Classification Codes: D2, D22, D220.